Predicting employment status in multiple sclerosis patients: the utility of the MS functional composite - Honarmand, Kimia; Akbar, Nadine; Kou, Nancy; Feinstein, Anthony (Journal of neurology, 2011)
As many as two-thirds of multiple sclerosis (MS) patients are unable to retain employment. Neurological and cognitive status are known to be significant predictors of unemployment, but the relationship between the two is unclear. Furthermore, the association between employment status and depression, anxiety, and personality has not been adequately explored in MS patients. This study examined the demographic, neurological, neuropsychological, and personality factors associated with unemployment in MS. We also sought to determine the utility of the Multiple Sclerosis Functional Composite (MSFC), a measure of MS-related disability incorporating physical and cognitive measures, in predicting employment status. A consecutive sample of 106 MS patients (61.3% unemployed) completed the Brief Repeatable Battery of Neuropsychological Tests (BRBN), Hospital Anxiety and Depression Scale (HADS), and NEO Five-Factor Personality Inventory. The MSFC emerged as the most robust predictor of employment status in MS patients, exceeding the predictive value of the EDSS. Together with NEO “Agreeableness” and HADS Depression subscore, the MSFC accounted for 49.8% of the variance in employment status. Unemployment was also associated with a progressive disease course, longer disease duration, and being female. While Global Cognitive Impairment did not differentiate between groups, unemployed patients scored significantly lower on three of five BRBN indices: Symbol Digit Modality Test, Paced Auditory Serial Addition Test, and Word List Generation. The findings highlight the utility of the MSFC as a predictor of unemployment in MS. Furthermore, a strong association was found between unemployment and the personality construct “Agreeableness”, and severity of depression.